2012
DOI: 10.3727/096368911x623880
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Endothelial Progenitor Cells with Osteopontin Enhances Cell Therapy for Peripheral Vascular Disease

Abstract: Tissue necrosis resulting from critical limb ischemia (CLI) leads to amputation in a significant number of patients. Autologous cell therapy using angiogenic cells such as endothelial progenitor cells (EPCs) holds promise as a treatment for CLI but a limitation of this treatment is that the underlying disease etiology that resulted in CLI may also contribute to dysfunction of the therapeutic EPCs. This study aimed to elucidate the mechanism of EPC dysfunction using diabetes mellitus as a model and to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…At 14 days a similar increase in angiogenic factors was observed, with the exception of FGF and NRP-2 that are unchanged compared with the control and an increase in osteopontin (OPN) and matrix metalloproteinase-8 (MMP-8) expression. Both OPN [59,60] and MMP-8 [61] have been proven to play important roles in angiogenesis in vitro and in vivo. The reduction in IL-10 expression, coupled with no change in IL-4 and IL-13 expression, indicates macrophages may be in a more pro-inflammatory phenotype compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…At 14 days a similar increase in angiogenic factors was observed, with the exception of FGF and NRP-2 that are unchanged compared with the control and an increase in osteopontin (OPN) and matrix metalloproteinase-8 (MMP-8) expression. Both OPN [59,60] and MMP-8 [61] have been proven to play important roles in angiogenesis in vitro and in vivo. The reduction in IL-10 expression, coupled with no change in IL-4 and IL-13 expression, indicates macrophages may be in a more pro-inflammatory phenotype compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Early EPCs or CACs are decreased in number and are dysfunctional in people with diabetes mellitus [30]. We have shown that the exposure of CACs to OPN rescues the angiogenic potential of OPN knockout CACs and restores blood flow in limb ischemia [18]. Using this strategy to restore the disease associated dysfunction associated with diabetic CACs, the wound healing benefit of CACs exposed to OPN was tested.…”
Section: Discussionmentioning
confidence: 99%
“…CACs isolated from people with diabetes demonstrate reduced angiogenic potential as demonstrated by reduced tubule formation in the matrigel assay. Diabetic CACs demonstrate reduced adhesion to matrix proteins and reduced migration [17,18]. Our group has recently observed decreased expression of the matricellular protein osteopontin (OPN) in CACs from patients with type 1 diabetes mellitus in the absence of microvascular or macrovascular complications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations